OP15 Improving The Osteoporosis Care Trajectory By Collaboration Between Clinicians, Patients And Health Insurers Within the Appropriate Care Program. (23rd December 2022) - Groeneveld, Iris; Witteveen, Janneke; Boonzajer-Flaes, Saskia; Mullenders, Pé; Leenen, Celine
Abstract : Introduction: The cyclic appropriate care program of the National Health Care Institute aims at enhancing quality of care in the Netherlands. A full cycle consists of four phases: (i) screening each ICD-10 chapter and selecting a care trajectory, (ii) in-depth analysis of the care trajectory and formulating actions for improvement, (iii) implementation, and (iv) evaluation. Collaboration with and between relevant parties from the field is key to its success. We describe the 2nd and 3th phase of this cycle, aimed at osteoporosis. Methods: First, nine clinicians, one nurse practitioner, two physiotherapists and one pharmacist representing scientific organizations, two patient representatives and one health insurer, defined research questions. Second, by in-depth analysis on declaration data of health care activities, and comparing the results to the guidelines, research questions were addressed. Last, results were discussed among all parties and actions for making wiser choices and improving the appropriateness of care were formulated. For each action, the parties defined who would take the lead and who would be involved. Results: The analyses showed that only 26 percent of Dutch fracture patients 50 years of age and above underwent dexa-scanning, as opposed to more than 80 percent in the guideline. All parties underlined this percentage should be increased. Possible actions were defined: to describe the care trajectory in the update of the multidisciplinary guideline; to better inform fracture patients about the importance of dexa-scanning; and to make adjustments to the hospital electronic system in order to facilitate the ordering of dexa-scans. For these actions, medical specialists were in the lead. Other data-analyses showed that half of osteoporosis patients stopped using medication within two years. For the jointly defined actions aimed at raising medication adherence, such as better patient education, the general practitioner and pharmacist were in the lead. Currently, the National Health Care Institute facilitates implementation and monitors improvement. Conclusions: Close collaboration with relevant parties led to well-considered actions on improvement of osteoporosis care.